KOMPETENSI, MOTIVASI KERJA, DAN KINERJA KARYAWAN PT. BLUE BIRD TBK KOTA BEKASI - Puspasari, Mardiana; Febriani, Yunita; Puspa Azahra, Yosefanny (MOTIVASI, 2024)
Purpose –The aim of the research is to determine the influence of competence and work motivation on the performance of PT employees. Blue Bird Tbk. (Pool Narogong) Bekasi City both simultaneously and partially. Design/methodology –This type of research used is associative research. The sample used in this study was 67 respondents from a total population of 200 permanent employees. The sampling technique used was the Proportionate Stratified Random Sampling technique. The data collection method used is through questionnaires and documentation. Data analysis used in this research is quantitative and qualitative data analysis, using a Likert scale. The data analysis technique used in this study is using multiple linear regression analysis, F test (simultaneous), t test (partial) and the coefficient of determination. Findings - The results of the research based on multiple linear regression show that competence and work motivation have a positive effect on the performance of employees at PT. Blue Bird Tbk. (Pool Narogong) Bekasi City. The results of the F hypothesis test show that there is a significant effect of competence and work motivation on the performance of employees of PT. Blue Bird Tbk. (Pool Narogong) Bekasi City. The results of the t hypothesis test show that there is a partial effect of competence and work motivation on the performance of employees of PT. Blue Bird Tbk. (Pool Narogong) Bekasi City. The results of the coefficient of determination show that the variables of competence and work motivation can contribute to the ups and downs of performance by 69.3%, while the rest are influenced by other variables not included in this study.